Co-inoculação de Rhizobium tropici e Azospirillum brasilense em feijoeiro cultivado sob duas lâminas de irrigação: produção e qualidade fisiológica de sementes - Peres, Amanda Ribeiro [UNESP] (2014)
The average yield of beans in Brazil is low. Alternatives that can increase yield in a sustainable manner should be preconized, such as reducing the use of nitrogen fertilizers through the adoption of biological nitrogen fixation. In this scenario, an alternative technique of co-inoculation or also called the mixed inoculation with symbiotic and non-symbiotic bacteria has been studied in leguminous, however there are few studies in field with common bean under the influence of the amount of water irrigated. Thus the objetive of this study was to evaluate the efficiency of inoculation and co-inoculation of common bean with Rhizobium tropici and Azospirillum brasilense under two irrigation depths on production and physiological seed quality. The experiment was performed in the fall/winter of the years 2012 and 2013, in Selviria-MS. A randomized block design in a 5x2 factorial scheme with four repetitions was used. The treatments were constituted by the combination of five forms of nitrogen supply (control non-inoculated with 40 kg ha- 1 of nitrogen in topdressing; control non-inoculated with 80 kg ha- 1 of N in topdressing; A. brasilense inoculation with 40 kg ha-1 of N in topdressing; R. tropici inoculation with 40 kg ha-1 of N in topdressing; and co-inoculation of A. brasilense and R. tropici with 40 kg ha- 1 of N in topdressing) and two irrigation depths (recommended and 75% of the recommended). Was concluded that the co-inoculation, the inoculation of R. tropici, the inoculation of A. brasilense associated with 40 kg ha-1 of nitrogen in topdressing and the control non-inoculation with application of 80 kg ha-1 of N topdressing not increase of grain yield compared to control non-inoculation with 40 kg ha-1 of nitrogen in topdressing. Considering the development conditions of the experiment, the use of 75% of the recommended irrigation depth provides similar or greater grain yield than the ...